THE The Role of Human Resource Capabilities in Enhancing Tourism in Banten Province - Zairil (PT. Hafasy Dwi Nawasena, 2024)
Banten Province, located at the western tip of Java Island, is a major tourist destination with various natural attractions, cultural heritage sites, and strategic coastal areas. Despite having attractions such as Ujung Kulon National Park, Tanjung Lesung Beach, and the historic city of Serang, the tourism sector in Banten faces major challenges related to the ability of human resources. This study examines the role of human resource capabilities in improving Banten's tourism sector by focusing on existing research gaps. The findings show significant skills shortages in customer service, digital literacy, and sustainable tourism practices. Current training programs are not enough to bridge these shortcomings, resulting in less than optimal service quality and limited innovation. In addition, there is a mismatch between the educational curriculum and the needs of the industry, as well as ineffective government support. The study recommends the development of tailored training programs, increased collaboration between educational institutions and tourism businesses, and more targeted government support to support sustainable tourism innovation and practices. By addressing these gaps, Banten's tourism sector is expected to improve its human resource capabilities, encourage innovation, and be more aligned with sustainable practices, which in turn can contribute to its growth and competitiveness.